2016
DOI: 10.1016/j.ssmph.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Multiple health behaviours among mothers and partners in England: Clustering, social patterning and intra-couple concordance

Abstract: Research on multiple health behaviours is increasing but little is known about parental behaviours and how they covary. Our study investigates cigarette smoking, alcohol intake, fruit and vegetable (F&V) consumption and physical activity among mothers and co-resident partners in England. Using the UK Household Longitudinal Study, we examined (i) clustering of health behaviours using observed-expected ratios and latent class analysis (ii) socio-demographic correlates of the derived latent classes and (iii) intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…smoke-free legislation implemented in 2007 (52)) within a different social context. However, similarities in HRB cluster patterns in this cohort when compared to other studies using more recent data (53,54) indicate that these HRB clusters remain relevant. For example, both of these studies and our results have identified a cluster (which we labelled 'Risky') characterised by heavy smoking and alcohol consumption and lower intakes of fruit and vegetables and levels (20).…”
Section: Strengths and Limitationssupporting
confidence: 59%
“…smoke-free legislation implemented in 2007 (52)) within a different social context. However, similarities in HRB cluster patterns in this cohort when compared to other studies using more recent data (53,54) indicate that these HRB clusters remain relevant. For example, both of these studies and our results have identified a cluster (which we labelled 'Risky') characterised by heavy smoking and alcohol consumption and lower intakes of fruit and vegetables and levels (20).…”
Section: Strengths and Limitationssupporting
confidence: 59%
“…However, a systematic review found that 81% of the identified studies reported a “healthy” cluster ( 3 ). Graham et al ( 74 ) examined clustering of fruit and vegetable consumption, physical activity, smoking, and alcohol intake of mothers and their partners in England and found “unhealthy” patterns for both mothers and their partner. In addition, they analyzed the concordance of behavioral patterns of mothers and their partners and found a high degree of inter-couple concordance in health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…All p values cited in the tables relate to this type of statistical testing. Following Graham et al (2014), observed-expected ratios were computed to assess the extent to which skin gambling and other forms of gambling cluster together. Observed-expected ratios are interpreted relative to their confidence intervals.…”
Section: Methodsmentioning
confidence: 99%